Maximizing Internal Sharia Resources: Innovation and Collaboration Strategies for Enhancing Bank Syariah Indonesia’s Business Performance - Thaib, Irwan; Puspaningrum, Astrid; Hussein, Ananda Sabil; Prabandari, Sri Palupi; Thaib, Ahmad Baariq (SCAD Independent, 2025)
Despite operating in a country with the world’s largest Muslim population, sharia banks in Indonesia face significant challenges in enhancing their business performance. Various perspectives highlight the critical role of internal resources in maximizing business performance. This study aims to analyze the impact of internal resources on the business performance of sharia banks in Indonesia, with innovation and collaboration strategies as mediating factors. The research was conducted at Indonesia’s largest sharia bank, employing a mixed-method approach that integrates qualitative and quantitative methodologies. Data from 462 participants were analyzed using structural equation modeling with the partial least squares method. The findings conceptualize sharia internal resources as a four-dimensional construct comprising operational, spiritual, infrastructural, and organizational capital. The results also confirm that sharia internal resources positively and significantly impact business performance, innovation strategy, and collaboration strategy. Furthermore, innovation and collaboration strategies significantly mediate this relationship, underscoring their strategic role in enhancing sharia banking performance. These findings expand the perspective on internal resources and their role in business performance, addressing a gap in the sharia banking literature.